1244Associations of endothelial function, arterial elasticity, and arterial stiffness with adiponectin and skeletal muscle mass. (2nd September 2021) - Agbaje, Andrew O.; Barker, Alan R.; Tuomainen, Tomi-Pekka
Abstract: Background: A temporal association where better arterial function and structure predicts adiponectin level and skeletal muscle mass during childhood remains uninvestigated. Methods: We studied 5566 children and adolescents (51% girls) aged 9-11 years from the Avon Longitudinal Study of Parents and Children (ALSPAC) birth cohort, Bristol, UK. Brachial artery endothelial function was determined using flow-mediated dilation (FMD), expressed as the percentage change in diameter from baseline after reactive hyperemia; arterial elasticity as distensibility coefficient (DC) expressed in mean percentage change in cross-sectional area relative to blood pressure (BP); and arterial stiffness by carotid to radial pulse wave velocity (crPWV). Skeletal muscle mass and total fat mass were assessed by dual-energy Xray absorptiometry. We conducted multivariable linear regressions with Sidak correction and adjusted for age, sex, total fat mass, cardiorespiratory fitness, pubertal status, brachial artery diameter, systolic BP, low-density lipoprotein cholesterol, mother's social-economic class, and time (years) between the measurement of predictors and outcomes. Results: FMD ( β [95% CI]) = (0.027 [0.007 to 0.047]; P = 0.009) and DC (0.229 [0.088 to 0.369]; P = 0.001) were directly associated with skeletal muscle mass. FMD had a borderline inverse association with adiponectin (-0.004 [-0.008 to < 0.0001]; P = 0.056). crPWV was unrelated to adiponectin and skeletal muscle mass, while DC was not associated with adiponectin. Conclusions: Better endothelial function and arterial elasticity were associated with higher skeletal muscle mass while arterial stiffness was unrelated to adiponectin and lean mass. Key message: Healthy arterial function and structure may enhance muscle growth in children.